Efek Pemberian Gentamisin Secara Oral Terhadap Kadar Asam Urat, Ureum, dan Kreatinin Tikus Wistar - Syahrul Ardiansyah (Universitas Muhammadiyah Surabaya, 2018)
ABSTRACTGentamicin is an aminoglycoside class of antibiotics which at high doses can cause damage to the kidneys. This research was to determine the levels of BUN, creatinine and amino acids after gentamicin induction. This research is experimental with gentamicin test material given to male rats as much as 0.3 ml/day for 7 and 10 days. Blood serum levels were then measured for BUN, creatinine and amino acids using a photometer microlab 300. The results showed that after doing treatment for 7 days the average value of BUN levels increase from 21.7 to 36.3 mg/dl, creatinine increase from 0, 88 to 1.9 mg/dl, uric acid increase from 1.54 to 4.29 mg/dl. It was concluded that giving of gentamicin as much as 0.3 ml/day for 7 and 10 days increased BUN levels, creatinine and uric acid exceeded the normal limit. Keywords : Gentamicin, urea, creatinine, uric acid, rat.